Geochronology and Stable Isotope Analysis of Fracture-Fill and Karst Mineralization Reveal Sub-Surface Paleo-Fluid Flow and Microbial Activity of the COSC-1 Borehole, Scandinavian Caledonides - Henrik Drake (Geosciences, 2020)
The deep biosphere hosted in fractured rocks within the upper continental crust is one of the least understood and studied ecological realms on Earth. Scarce knowledge of ancient life and paleo-fluid flow within this realm is owing to the lack of deep drilling into the crust. Here we apply microscale high spatial-resolution analytical techniques to fine-grained secondary minerals in a deep borehole (COSC-1) drilled into the Silurian-Devonian Scandinavian Caledonide mountain range in central Sweden. The aim is to detect and date signs of ancient microbial activity and low-temperature fluid circulation in micro-karsts (foliation-parallel dissolution cavities in the rock) and fractures at depth in the nappe system. Vein carbonates sampled at 684 to 2210 m show a decreased C isotope variability at depths below 1050 m; likely due to decreased influence of organic-C at great depth. Micro-karsts at 122−178 m depth feature at least two generations of secondary calcite and pyrite growth in the voids as shown by secondary ion mass spectrometry analytical transects within individual grains. The younger of these two precipitation phases shows 34S-depleted δ34Spyrite values (−19.8 ± 1.6‱ vs. Vienna-Canyon Diablo Troilite (V-CDT)) suggesting microbial sulfate reduction in situ. The calcite of this late phase can be distinguished from the older calcite by higher δ18Ocalcite values that correspond to precipitation from ambient meteoric water. The late stage calcite gave two separate laser ablation inductively coupled mass spectrometry-derived U-Pb ages (9.6 ± 1.3 Ma and 2.5 ± 0.2 Ma), marking a minimum age for widespread micro-karst formation within the nappe. Several stages of fluid flow and mineral precipitation followed karst formation; with related bacterial activity as late as the Neogene-Quaternary; in structures presently water conducting. The results show that our combined high spatial-resolution stable isotope and geochronology approach is suitable for characterizing paleo-fluid flow in micro-karst; in this case, of the crystalline crust comprising orogenic nappe units.